Living Donor Liver Transplantation With Augmented Venous Outflow and Splenectomy: A Promised Land for Small Left Lobe Grafts. Issue 5 (27th November 2022) - Fujiki, Masato; Hashimoto, Koji; Quintini, Cristiano; Aucejo, Federico; Kwon, Choon H.D.; Matsushima, Hajime; Sasaki, Kazunari; Campos, Luis; Eghtesad, Bijan; Diago, Teresa; Iuppa, Giuseppe; D'amico, Giuseppe; et al.
Abstract : Objective: Living donor liver transplantation (LDLT) using small grafts, especially left lobe grafts (H1234-MHV) (LLG), continues to be a challenge due to small-for-size syndrome (SFSS). We herein demonstrate that with surgical modifications, outcomes with small grafts can be improved. Methods: Between 2012 and 2020, we performed 130 adult LDLT using 61 (47%) LLG (H1234-MHV) in a single Enterprise. The median graft-to-recipient weight ratio was 0.84%, with graft-to-recipient weight ratio <0.7% accounting for 22%. Splenectomy was performed in 72 (56%) patients for inflow modulation before (n=50) or after (n=22) graft reperfusion. In LLG-LDLT, venous outflow was achieved using all three recipient hepatic veins. In right lobe graft (H5678) (RLG)-LDLT, the augmented graft right hepatic vein was anastomosed to the recipient's cava with a large cavotomy. Outcome measures include SFSS, early allograft dysfunction (EAD), and survival. Results: Graft survival rates at 1, 3, and 5 years were 94%, 90%, and 83%, respectively, with no differences between LLG (H1234-MHV) and RLG (H5678). Splenectomy significantly reduced portal flow without increasing the complication rate. Despite the aggressive use of small grafts, SFSS and EAD developed in only 1 (0.8%) and 18 (13.8%) patients, respectively. Multivariable logistic regression revealed model for end-stage liver disease score and LLG (H1234-MHV) as independent risk factors for EAD and splenectomy as a protective factor (odds ratio: 0.09; P =0.03). For LLG (H1234-MHV)-LDLT, patients who underwent prereperfusion splenectomy tended to have better 1-year graft survival than those receiving postreperfusion splenectomy. Conclusions: LLG (H1234-MHV) are feasible in adult LDLT with excellent outcomes comparable to RLG (H5678). Venous outflow augmentation and splenectomy help lower the threshold of using small-for-size grafts without compromising graft survival.